The Chemodynamics of the Stellar Populations in M31 from APOGEE Integrated-light Spectroscopy - Benjamin J. Gibson; Gail Zasowski; Anil Seth; Aishwarya Ashok; Kameron Goold; Tobin Wainer; Sten Hasselquist; Jon Holtzman; Julie Imig; Dmitry Bizyaev; Steven R. Majewski (The Astrophysical Journal, 2023)
We present an analysis of nearly 1000 near-infrared, integrated-light spectra from APOGEE in the inner ∼7 kpc of M31. We utilize full-spectrum fitting with A-LIST simple stellar population spectral templates that represent a population of stars with the same age, [M/H], and [ α /M]. With this, we determine the mean kinematics, metallicities, α abundances, and ages of the stellar populations of M31's bar, bulge, and inner disk (∼4–7 kpc). We find a nonaxisymmetric velocity field in M31 resulting from the presence of a bar. The bulge of M31 is less metal-rich (mean [M/H] = $-{0.149}_{-0.081}^{+0.067}$ dex) than the disk, features minima in metallicity on either side of the bar ([M/H] ∼ −0.2), and is enhanced in α abundance (mean [ α /M] = ${0.281}_{-0.038}^{+0.035}$ ). The disk of M31 within ∼7 kpc is enhanced in both metallicity ([M/H] = $-{0.023}_{-0.052}^{+0.050}$ ) and α abundance ([ α /M] = ${0.274}_{-0.025}^{+0.020}$ ). Both of these structural components are uniformly old at ≃12 Gyr. We find the mean metallicity increases with distance from the center of M31, with the steepest gradient along the disk major axis (0.043 ± 0.021 dex kpc ^−1 ). This gradient is the result of changing light contributions from the bulge and disk. The chemodynamics of stellar populations encodes information about a galaxy’s chemical enrichment, star formation history, and merger history, allowing us to discuss new constraints on M31's formation. Our results provide a stepping stone between our understanding of the Milky Way and other external galaxies.